Meta-Analysis: Obesity, Smoking, and Alcohol Consumption as risk Factors of Breast Cancer - Yuliana Yuvrista; Wiwit Marliana (Masters Program in Public Health, 2022)
Background: Breast cancer is a type of cancer that is the main cause of death in women. Breast cancer is classified as a non-communicable disease that requires a long time for the development of cancer cells in the patient's body with various risk factors that are multifactorial. Several incidences of breast cancer are often associated with risk factors for an unhealthy lifestyle, including frequent consumption of fast food, less consumption of fruits and vegetables, lack of exercise, alcohol consumption, etc. This study aims to analyze the effect of obesity, smoking, and alcohol consumption on the risk of breast cancer in women.Subjects and Method: This study used a systematic review of meta-analysis. Data search was carried out using electronic databases consisting of: PubMed, Science Direct, Europe PMC and Google Scholar with the search keywords used were